Digital social media expression and social adaptability of the older adult driven by artificial intelligence - Gao, Yuan; Liang, Jiahui; Xu, Zhengbing (Frontiers in Public Health, 2024)
This study examines the potential impact of digital new media art on the health literacy and digital health literacy of older adults. It begins by outlining how digital new media art is expressed and its effects on the social adaptability of the older demographic. The research methodology includes conducting interviews and observations with elderly participants in communities A and B to identify variations in their use of smartphones, engagement in community activities, and access to community technological infrastructure. Furthermore, the study investigates their usage of digital new media in various domains such as interpersonal communication, information retrieval, entertainment, practical applications, and mobile payment systems. The findings reveal distinct differences in digital new media art engagement among the elderly. Those with prior computer experience tend to be more adept at using smartphones and more active in community events, suggesting that digital new media art can significantly enhance community participation among the elderly. In contrast, elderly individuals in community B displayed a lower acceptance of digital new media art, with no clear link to their participation in community activities. Additionally, the research highlights substantial variability in the use of digital media for information retrieval, entertainment, practical applications, and mobile payments. Some elderly are proficient in leveraging these technologies, while others are more reserved. Analysis of their engagement with digital content like short videos, online financial management, and social media indicates that digital new media art not only augments the cultural and spiritual lives of the elderly but also bolsters their social adaptability. Overall, addressing these disparities is essential for ensuring that all older adults can benefit from advancements in digital technologies, enhancing their health literacy, and overall well-being in today's increasingly digital society. This study provides valuable insights into the adaptation of elderly individuals to the digital new media landscape and suggests directions for future development of digital new media art expressions.